SELECTION OF THE BEST RIDE-HAILING BY USING ANALYTIC HIERARCHY PROCESS - Saripudin Saripudin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The online-based or ride-hailing service business in Indonesia continues to develop and metamorphose into multifunctional transportation services, this development makes it difficult for customers to determine alternatives to the top two ride hailing services, namely Goride and Grabbike. For this reason, the purpose of this study is to make decisions based on performance, service, security, price, promo and branding criteria to determine the best and make it easier to choose the transportation. The method used is the Analytic Hierarchy Process (AHP) model with the help of Super Decisions software. The data sampling technique was carried out by distributing online questionnaires of 100 respondents to the public using transportation services. The results of this research indicate criteria and alternatives. Shows the Safety Criteria 36.02%, Service Criteria 23.73%, Price Criteria 16.36%, Promo Criteria 11.29%, Performance Criteria 7.79%, Branding Criteria 4.81%. It seems that security is the most important factor for potential customers because it is related to customer safety, while the two most popular alternatives to Goride and Grabbike are Grabbike. Where GrabBike is superior in terms of cheap prices per kilometer and good branding and everywhere, while Gojek excels in terms of services provided to customers.